Assessing the experiential marketing and customer value to develop the customer satisfaction - Siagian, Hendra Sakti Putra; Octoyuda, Edgar (Forum Kerjasama Pendidikan Tinggi, 2024)
Customer loyalty refers to the dedication of a customer to consistently utilize the products or services of a particular company on a voluntary basis in the future. The achievement of this is inextricably linked to experiential marketing elements, customer value, and customer gratification, all of which marketers employ when attempting to sell products and services to consumers. This investigation was conducted in the North Sumatra region with specialist physicians as end users of pharmaceutical company products. The primary objective of this study is to investigate the relationship between customer value and customer satisfaction, as well as to assess the effect of customer value as a mediator between customer satisfaction and experiential marketing. The methodology employed a quantitative non-probability sampling strategy, resulting in the acquisition of 212 respondents. Through social media distribution of questionnaires, data is gathered. For assessing variable data, a Likert scale is utilized. Utilizing SmartPLS 3.0 and structural equation modeling (SEM), the data analysis method employs SEM. Customer value mediates the relationship between experiential marketing and customer satisfaction, as determined by the analysis's findings. Customer value and experiential marketing both have a positive impact on customer satisfaction. The company has integrated customer value and experiential marketing implications into one of its strategies to enhance physician satisfaction